2021
DOI: 10.3991/ijoe.v17i03.20369
|View full text |Cite
|
Sign up to set email alerts
|

Designing A Smart Monitoring and Alert System for Malaria Patients Based on IoT in Burundi

Abstract: Malaria is an infectious disease that has a devastating effect on humans but is contagious and preventable. There were 228 million malaria cases globally in 2018, with 93% of patients and 94% dying showing up in Africa within Burundi, possessing a massive growth (51%). This study proposes an IoT design for smart monitoring and alert systems for malaria patients in Burundi. After being tested positive while they are home drinking tablets prescribed by the doctor, the patients will use a body temperature sensor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The application passed the MAST test, proving that the created telemedicine solution for cardiac patients serves its secondary prevention goal. Sabukunze et al [28] proposed an IoT concept for smart malaria patient monitoring and alert systems. They concluded that a smart monitoring and alert system is critical for monitoring malaria patients and can warn them in the event of a serious situation.…”
Section: Introductionmentioning
confidence: 99%
“…The application passed the MAST test, proving that the created telemedicine solution for cardiac patients serves its secondary prevention goal. Sabukunze et al [28] proposed an IoT concept for smart malaria patient monitoring and alert systems. They concluded that a smart monitoring and alert system is critical for monitoring malaria patients and can warn them in the event of a serious situation.…”
Section: Introductionmentioning
confidence: 99%
“…In such circumstances, the use of Internet of Things (IoT) technologies ultimately helps the development of smart systems to support and improve the processes related to biomedical and healthcare that is essential for elderly NCD patients [7]. An intelligent health support system meant for patient surveillance even in quarantines requires utilizing IoT based smart home healthcare to treat and monitor NCDs and "for decreasing needless troubles on hospitals caused by infectious diseases" [11]. Medical care can be significantly revolutionised through IoT usage.…”
Section: Introductionmentioning
confidence: 99%